Synergistic interaction of education, science, and industry - Vladimir Klimuk; Anna Tarasova; Yulia Kuznetsova; Laura Dzhabrailova (Leadership, Education, Personality. An Interdisciplinary Journal, 2020)
Economic and social development of a country rely on advanced science and technology, skilled, educated workforce, extensive growth of innovation and population density. The process of innovation creation can be long and winding and should take into account the needs of technological development and definitely bring benefits to business. The concept of a science park has not been new. The United States of America were pioneers who in early 1950s suggested a brand new model for bridging the gap between academia and industry. Nowadays developed countries employ that model, though its objectives, funds, inputs and outcomes may vary. This paper will focus of the issue of real interaction of institutions of education, science and industry and will raise a number of controversial issues in the correction of the vector for socio-economic modernization. The authors analyzed a set of legislation acts on regulating the cooperation of academia and business. The paper gives a graphical model of reciprocity of institutions of education, science, and industry taking into account the interests of public authorities, and offers a set of additional indicators of evaluation of the efficiency of functioning of an innovation structure in the country (region).
Keywords: 330; Innovation infrastructure; Interaction of education; science; and industry; Synergistic effect; Indicators of evaluation of interaction efficiency